An analysis of flexible cystoscopic findings among patients visiting Urology outpatient services at a tertiary cancer center in Nepal - Nepal, Umesh; Pokharel, Bharat Mani; Pradhan, Sulav; Gharti, Binod Babu; Pokharel, Gyan Prasad; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2023)
Introduction: Cystoscopy is a common urological procedure done for diagnosis and surveillance of patients with urological ailments. With various lower urinary tract symptoms, flexible cystoscopy can be performed with a minimal discomfort to the patient and in a outpatient setting under local anesthesia. Materials and Methods: We retrospectively analyzed 468 patients undergoing flexible cystoscopy from January 2022 to July 2022 over a period of six months in the outpatient services of B.P. Koirala Memorial Cancer Hospital. Results: Majority of the patients (56.2%) had some pathology of the lower urinary tract among which urinary bladder mass or malignancy was the predominant findings with 35%. Conclusion: Flexible cystoscopy is an important tool in urology with high diagnostic yield.